Evaluating Rural Electrification Projects - Methodological Approaches - Jörg Peters (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
In recent years, the international community has expanded efforts in programme evaluation to improve the accountability of development projects. This paper presents approaches to implementing state-of-the-art evaluations in rural electrification projects, taking into account specific challenges that researchers face in such interventions. Furthermore, it suggests a particular approach to assess impacts before an intervention is implemented by surveying the yet non-electrified target region of the project and, in addition, an already electrified region. Besides delivering robust evidence on impacts, results from such ex-ante evaluations provide insights for the project design, thereby reducing the gap between evaluation researchers and practitioners.
Keywords: O12; O22; C31; C81; 330; Impact evaluation; ex-ante impact assessment; electricity access; rural development; Elektrizitätspolitik; Ländlicher Raum; Entwicklungsprojekt; Projektbewertung; Wissenschaftliche Methode; Theorie; Entwicklungsländer; Afrika